2012
DOI: 10.1177/2047487312437057
|View full text |Cite
|
Sign up to set email alerts
|

Participating or not in a cardiac rehabilitation programme: factors influencing a patient’s decision

Abstract: Our findings demonstrate the importance of raising patients' awareness of the benefits of CR. Addressing potential barriers to attend a CR programme should be investigated with patients individually in order to ensure compliance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
80
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(92 citation statements)
references
References 31 publications
3
80
2
1
Order By: Relevance
“…The reasons for this range from the perception that the CR program may not be suitably designed to meet the needs of the elderly, to reasons such as physical impairments and lack of transportation. 34 The relationship between gender and attendance, is less clear but several studies have reported a higher attendance among males. 32,35 Distance from the CR center and lack of transportation were among the chief reasons across studies for nonattendance.…”
Section: Challenges With Referral and Attendancementioning
confidence: 97%
See 2 more Smart Citations
“…The reasons for this range from the perception that the CR program may not be suitably designed to meet the needs of the elderly, to reasons such as physical impairments and lack of transportation. 34 The relationship between gender and attendance, is less clear but several studies have reported a higher attendance among males. 32,35 Distance from the CR center and lack of transportation were among the chief reasons across studies for nonattendance.…”
Section: Challenges With Referral and Attendancementioning
confidence: 97%
“…33 For women, often these were the most frequently reported reasons for not attending CR. 34 Several studies have reported on the importance of physician endorsement in the decision to participate in CR. The inpatient experience and interaction with other healthcare providers influenced a patients' decision to attend CR.…”
Section: Challenges With Referral and Attendancementioning
confidence: 99%
See 1 more Smart Citation
“…8Y10 In addition, a considerable number of those patients who actually attend CR drop out prematurely varying from 22% to 65%. 11,12 This may be partly due to personal (perception of self-control of the problem, illness cognition, socioeconomic status) or financial reasons, 9,11,13,14 but also physical and psychological health problems may play a key role. 9,12 The majority of these studies 11,12,14 have often focused on a particular subgroup of cardiac patients who may not always be representative for the total CR population.…”
mentioning
confidence: 99%
“…Cardiac rehabilitation, in addition to improving functional status cost-effectively (28,29), has a protective effect against cardiac events further preserving function and working ability (30,31). Improving participation in cardiac rehabilitation programs can be difficult, but attendance can be improved by addressing system-and patient-level barriers (32) while physical barriers other than coronary disease, such as those prevalent in the current study population, can still prevent attendance (33). It is also noteworthy that the deleterious effects of incomplete revascularization can also be mitigated by rehabilitation, and cardiac rehabilitation improves adherence to secondary prevention (34).…”
Section: Discussionmentioning
confidence: 99%